Placental glucocorticoid receptors are not affected by maternal depression or SSRI treatment. (2nd January 2020) - Edvinsson, Åsa; Hoyer, Angela; Hansson, Malin; Kallak, Theodora Kunovac; Sundström-Poromaa, Inger; Skalkidou, Alkistis; Lager, Susanne
Abstract: Background: Prenatal depression is common, with an estimate that up to one in five pregnant women suffers from depressive symptoms. Maternal depression is associated with poor pregnancy outcomes such as preterm birth and low birth-weight. Such outcomes possibly affect offspring development. Previous studies suggest placental RNA levels of the glucocorticoid receptor are altered by maternal depression or anxiety; this stress may affect the placenta of male and female foetuses differently. However, it is unknown if the protein levels and activity of this receptor are additionally affected in women with depressive symptoms or being pharmacologically treated for depression. Methods: In this study, we investigated whether the glucocorticoid receptor (NR3C1) in the placenta is affected by maternal depression and/or selective serotonin reuptake inhibitor (SSRIs) treatment. Placentas from 45 women with singleton, term pregnancies were analysed by Western blot to determine glucocorticoid receptor levels, and by DNA-binding capacity to measure glucocorticoid receptor activation. Results: There were no differences in levels of the glucocorticoid receptor or activity between groups (control, depressive symptoms, and SSRI treatment; n  = 45). Similarly, there was no difference in placental glucocorticoid receptor levels or activity dependent upon foetal sex. Conclusion: Maternal depression and SSRI treatment do not affect the glucocorticoid receptors in the placenta.